Post Ischemic Administration Of Dihydrokainate, A Glt-1 Blocker Fails To Attenuate Transient Focal Cerebral Ischemia Evoked Neurodegeneration In Rats - P. KALAIVANI; GIRISH RAMESH; R. BARATHIDASAN; C. SARAVANA BABU (International Journal of Pharma and Bio Sciences, 2015)
Recently modulation of the GLT-1 transporter has been extensively focussed in various models of ischemic injury for evaluating neuroprotection. Therefore an attempt was made to study the neuroprotective effect of dihydrokainate (DHK) – a GLT-1 transporter blocker in transient focal cerebral ischemia model of Sprague Dawley rats during post ischemic phase. 2 h of ischemia – 70 h of reperfusion significantly induced neurological deficit, elevated glutamate levels, depleted bioenergetics levels (NAD+ and ATP), displayed heinous oxidative stress (increase of nitrite/nitrate and TBARS content, reduced glutathione and superoxide dismutase levels), increased expression of PARP1, Caspase-3 and decreased expression of SIRT1 along with neuronal damage with decreased nissl positive cells. Post ischemic administration of DHK significantly reversed neurological deficits; however failed to reverse the biochemical alterations, bioenergetics levels and expression of bioenergetics regulators. Based on our present findings, the authors concluded that post ischemic phase is not the suitable therapeutic regimen for DHK.